Mesozooplankton of an impacted bay in North Eastern Brazil - Silva,Andréa Pinto (2004)
Mesozooplankton abundance and distribution at Suape Bay, Pernambuco, was studied to assess the impacts caused by the construction of an internal port to increase the capacity of the Suape Port Complex. Zooplankton sampling was done at 3 stations during the dry (November-December/1997) and rainy (April-May/1998) seasons. A plankton net with 300 µm mesh size was used. Wet weight plankton biomass ranged from 44 mg.m-3 to 3,638 mg.m-3. Forty-five macrozooplankton taxa were registered. The most abundant was Copepoda. Among copepods, Acartia lilljeborgi, Parvocalanus crassirostris, Oithona hebes, Corycaeus (C.) speciosus and Temora turbinata were most frequent. Minimum abundance was 9 ind.m-3 and maximum was 2,532 ind.m-3. Average species diversity was 2.55 bits.ind-1. As a whole, Suape Bay has been under severe environmental stress and it seemed reasonable to assume that the recent modifications of the basin have resulted in changes in species composition and trophic structure, with an increase in marine influence.